A two-parameter correlation for predicting oil recovery factor in water-drive reservoirs (1994)
A simple correlation has been developed for estimating primary recovery factors for Niger Delta oil reservoirs. The correlation which was developed, from data collected across the Niger Delta, is valid for reservoirs with strong water drives. Only two major parameters are required for the recovery factor calculations in this work, unlike other multi-parameter correlations. This makes this correlation very easy to apply. An expression has also been included for predicting residual oil saturation, where core or log analysis data are not available. The results obtained using these models have been compared with other published models, and applied to many case studies, with better predictions. Graphical and statistical error analyses also confirm good correlations. These correlations should also, yield good predictions for reservoirs from other regions that have similar reservoir and fluid characteristics.